Psychological study of the development of advanced training of students - Сматова, Клара; Балтабаева, Аружан (Pedagogy and Psychology, 2022)
In the period of modern global changes, one of the topical issues has become a psychological study of the development of assertive behavior of students. It has been comprehensively studied that assertive behavior includes the qualities of the ability to defend their rights and regulate their behavior, regardless of external influences. The importance of rational use of smart resources in the formation of assertiveness, conflict control in communication, and independent decision-making is determined. Since Bullying is an undesirable aggressive behavior, it has been proven that it negatively affects assertive behavior, so the ability to cope with stress, self-confidence are effective ways to form and achieve assertiveness. The following research methods were applied: analysis of scientific and theoretical, psychological literature, discussion, questionnaires "Assertiveness", "Diagnosis of assertive behavior", S. Hobfall's methodology "Strategies for overcoming stressful situations", processing of the data obtained. The study implements the development of assertive behavior of students through three main factors, including the presence of important psychological qualities: cognitive activity, socio-motivational, communicative activity and internal unity of emotional and volitional stability.